Host proteases: key regulators in viral infection and therapeutic targeting - Xia, Qiongrong; Liu, Xiaohua; Huang, Huacui (Frontiers in Immunology, 2025)
Viral infections pose a major threat to global health, causing severe pneumonia, meningitis, hepatitis, and fatal complications. Viruses are highly dependent on host cellular factors to complete their life cycle, and host proteases, as one of the core regulatory hubs, profoundly influence the progression of infection and pathogenicity. Viruses rely on specific host proteases (e.g., transmembrane serine proteases [TMPRSS family], furin, cathepsins, and others such as caspases and metalloproteases) to precisely cleave and activate viral surface glycoproteins and internal precursor proteins, thereby facilitating efficient invasion, replication, release, and immune evasion. Meanwhile, host proteases participate bidirectionally in immune regulation. They can be exploited by viruses to exacerbate pathological damage (e.g., triggering cytokine storms), yet also act as key defense components by directly cleaving viral proteins to inhibit infection. Different viruses have evolved sophisticated strategies to hijack host proteases, whose activity, specificity, and tissue distribution directly determine the viral tissue tropism and pathogenic potential. Compared to highly mutable viral targets, host proteases serve as ideal targets for developing host-directed antiviral drugs (HADs) due to their genetic stability and conserved mechanisms, but their toxicity requires careful evaluation because of their physiological roles. Inhibitor strategies targeting host proteases have demonstrated promising breakthrough potential in circumventing drug resistance and exerting broad-spectrum inhibitory activity against diverse viruses. Elucidating the multidimensional roles of host proteases in infection is crucial for designing the next-generation of broad-spectrum, anti-drug resistance antiviral strategies. This review systematically summarizes the regulatory mechanisms of host proteases at various stages of viral infection and advances in targeted intervention strategies, providing theoretical support for the development of resistance-resistant and broad-spectrum antiviral therapeutics.